Pengaruh Tanaman Bintang Air (Cyperus Papyrus) Dan Bambu Air (Equisetum Hyemale) Dalam Mengolah Limbah Domestik - Muhammad Al Kholif; Syahrul Hidayat; Joko Sutrisno; Suning Suning (Jurnal Serambi Engineering, 2020)
One of the technologies that will be used to overcome the problem of environmental pollution due to the generation of greywater is by applying Constructed Wetlands using aquatic plants. Aquatic plants that will be used in this study are using Bintang Air (Cyperus papyrus) and Bambu Air (Equisetum hyemale) plants. The purpose of this study was to determine the effectiveness of decreasing BOD5 and COD parameters and comparing the ability of each plant to absorb pollutants in greywater. The results showed that the Bintang Air (Cyperus papyrus) plant was able to set aside BOD5 levels of 97.14% while the efficiency of COD levels was 95.43%. At Bambu Air (Equisetum hyemale) it is able to set aside BOD5 levels by 90.34% while efficiency for COD is 89.67%. When viewed from the ability of the two types of plants to absorb pollutants in domestic wastewater, the Bintang Air (Cyperus papyrus) plant is superior in absorbing pollutants than the Bambu Air (Equisetum hyemale) plant.